Madagascar : Decentralization - World Bank (Washington, DC, 2013)
The objective of this decentralization study is to provide analysis and policy advice to the new Malagasy government on how to proceed with the decentralization strategy it inherited from the previous government. The end of the post-crisis emergency recovery period creates the opportunity to correct the weaknesses of the previous strategy while building on the exiting achievements. The paper specifically aims to (i) analyze the institutional and fiscal context of decentralization and (ii) present the resulting challenges for service delivery and financing - with a particular focus on local governments. Benefiting from primary data from several hundred local governments, this study aims at proving recommendations of how to improve the functioning of communes in considering the institutional and fiscal parameters. The report is organized into four chapters, including the Introduction, which explain the political, institutional, and fiscal determinants that have been influencing Madagascar's decentralization process, and which will continue to do so in the future. Chapter 2 provides the political and institutional background needed to better understand the decentralization context of today. The chapter analyzes the historical forces of centralization, which date back to pre-colonial times and translate into today's dominant role of the central government administration. The chapter then takes a closer look at the existing administrative set-up to explain functions and responsibilities at different levels of government. To this end, it looks at the regulatory gaps and inconsistencies in the legal framework, the parallelism between decentralized and deconcentrated layers, and the emerging role of inter- communal associations and informal regional planning bodies. Based on the concept of the sub-national fiscal gap, chapter 3 analyzes structural constraints to fiscal decentralization in Madagascar, and in particular the dominance of revenue items which cannot be decentralized. Given the l o w degree of fiscal decentralization, the chapter takes a closer look at expenditure deconcentration and provides a more in-depth analysis of deconcentration in the health and education sectors. The last part of the chapter evaluates Madagascar's intergovernmental transfers, which represent the most important source of local government financing. Communes are the lowest and institutionally most advanced level of sub-national government in Madagascar. They are also the main focus of this study. The fourth chapter describes the institutional dynamics at the local level to provide the ground for a thorough analysis of local government finance. The chapter provides an estimate of local needs, and analyzes revenue and expenditure patterns based on budget data of a large sample of rural communes.